2018
DOI: 10.1111/jhn.12601
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analysis of nutrition interventions for chronic noncancer pain

Abstract: Background: This systematic review aimed to evaluate the impact of nutrition interventions on participant reported pain severity and intensity in populations with chronic pain. Methods: Eight databases were systematically searched for studies that included adult populations with a chronic pain condition, a nutrition intervention and a measure of pain. Where possible, data were pooled using meta-analysis. Seventy-one studies were included, with 23 being eligible for meta-analysis. Results: Studies were categori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(73 citation statements)
references
References 86 publications
(737 reference statements)
1
68
0
4
Order By: Relevance
“…Our study was unique in that it included both naïve and stressed conditions, female and male mice, and quantities of anti-inflammatory compounds that are realistically attainable in the human diet (46). There is evidence that this type of dietary intervention may translate well to humans as a recent systematic review (47) found that nutritional interventions significantly reduced pain scores, although the specific interventions were varied and additional high-quality clinical trials are needed. The inclusion of both sexes in this study led to some interesting albeit expected sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…Our study was unique in that it included both naïve and stressed conditions, female and male mice, and quantities of anti-inflammatory compounds that are realistically attainable in the human diet (46). There is evidence that this type of dietary intervention may translate well to humans as a recent systematic review (47) found that nutritional interventions significantly reduced pain scores, although the specific interventions were varied and additional high-quality clinical trials are needed. The inclusion of both sexes in this study led to some interesting albeit expected sex differences.…”
Section: Discussionmentioning
confidence: 99%
“…Yet few treatment programs take diet or weight status into account, and treatment can be complicated . This is a shortcoming, as recent meta‐analysis confirmed that nutritional interventions, especially altered dietary pattern and altered specific nutrients, result in significant pain relief in people having chronic pain . Studies regarding dietary interventions in people having chronic pain are primarily in people with osteoarthritis and indicate a superiority of multimodal over single‐mode interventions.…”
Section: Diet and Related Overweight In People With Chronic Painmentioning
confidence: 99%
“…Dietary behaviour and dietary intake are lifestyle factors that might influence the occurrence, maintenance, and perception of chronic musculoskeletal pain [21][22][23]. For instance, overweight and obesity are suggested as two main associated factors of unhealthy dietary behaviour and are two main aspects of nutritional status in patients with chronic musculoskeletal pain [24].…”
Section: Introductionmentioning
confidence: 99%